Visual histories: Photography in the popular imagination - Karlekar, Malavika (New Delhi, 2013)
Divided into two sections, the thirty-two essays, illustrated with archival photographs, look at the camera in the colonial era and in post-Independence India. The first section looks at photography through 'The Colonial Eye', with the camera and the studio becoming necessary prostheses in the new engagement between the colonized and the rulers in the nineteenth century. Europeans, of whom the British were the largest in number, were the initial users of the photographic studio and early studio images of the sahib civil servant, lawyer, tea planter, missionary and so on are among the first available visuals. The second section of the volume, looks at some such moments as well as takes the viewer to Independence and the years beyond.
Keywords: Social history, Photography